Comparison of the anesthetic effects of remimazolam tosilate and remimazolam besylate in daytime hysteroscopic surgery - Huan Zhang; Min Fu; Fangli Yue; Yaxin Wei; Xinyuan Shi; Shiyu Yu; Fanceng Ji (BMC Anesthesiology, 2024)
Abstract Objective The purpose of this study is to observe whether there is a difference in the anesthetic effect of remimazolam tosilate and remimazolam besylate in daytime hysteroscopic surgery, so as to provide reference for clinical application. Methods Fifty patients, aged 18–65 years, ASA I-II, scheduled for hysteroscopy under total intravenous anesthesia were selected. The patients were randomly divided into two groups (n = 25): remimazolam tosilate group (group T) and remimazolam besylate group ( group R). The main observation index was the induction dose of remimazolam; secondary observation indicators were sleep time, anesthesia maintenance time, recovery time, induction maintenance dose of alfentanil, maintenance dose of remimazolam, and incidence of adverse events during anesthesia ( hypertension, hypotension, bradycardia, tachycardia). Results There was no significant difference in anesthesia induction dose, recovery time, sleep time, anesthesia maintenance time, and incidence of adverse events during anesthesia ( body movement, cough, hypertension, hypotension, bradycardia, tachycardia) between the two groups (P > 0.05). Conclusion There was no significant difference in the anesthetic effect of remimazolam tosilate and remimazolam besylate in daytime hysteroscopic surgery. Clinical trial Registration Chinese Clinical Trial Registry, ChiCTR2400081688.